Eruption Sequences and Characteristics of Weizhou Island Volcano, Guangxi Province, South of China - Yu, Hongmei; Yang, Wenjian; Zhao, Bo; Chen, Zhengquan; Zhou, Bin; Nie, Guanjun; Luo, Hao (Frontiers in Earth Science, 2021)
Weizhou island, located in the north margin of the South China Sea (SCS), is characterized by multi-stage volcanism, several eruption styles and eruption craters, and is also the youngest Quaternary volcanic island in China. An eruption on this island may pose high risk to life and property. However, the eruptive history of Weizhou island, the craters number and location, and their eruptive sequence and characteristics are still being debated, which are important for potential volcanic hazard assessment. In the present study, field surveys, 40Ar/39Ar and 14C geochronological studies and whole rock composition analysis of volcanic rock are used to investigate the eruption sequences associated with Weizhou island and the characteristics of each period. Four volcanoes were discovered at Henglushan, Hengling, Nanwan and Daling. The Henglushan and Hengling volcanoes were produced by early weak explosive and late effusive eruptions, and lavas from these volcanoes represent the foundation of island. Conversely, the Nanwan and Daling volcanoes are linked to multiple explosive eruption phases, with hydromagmatic eruptions in the first and last phase and a magmatic explosive eruption in the second phase. The pyroclastic density currents (PDCs) deposits of the Nanwan and Daling volcanoes virtually cover the entire island. Volcanic activity in Weizhou island started in Early Pleistocene and ended in Late Pleistocene. This can be divided into the following distinct periods: 1,420–1,260, 870–740, 600–480, 283–222 ka, and 33.7–13 ka. The first four periods were dominated by effusive eruptions associated with the Henglushan and Hengling volcanoes, which peaked between 870 and 740 ka. After this period, explosive eruptions began at around 33.7 ka because of magma–water interactions. These explosive eruptions then created the Nanwan and Daling volcanoes. Early effusive lava flows in Weizhou island are characterized by basaltic compositions and are linked with a small amount of fractional crystallization. Magmas in later eruptions contained slightly lower SiO2 and involved some basanite. Fractional crystallization was also less pronounced in these lavas because of their rapid ascent.